Heating and ventiliation - Blachly, Minerva (My University, 1900)
Introduction: Only twenty-five years ago, little attention was paid to the proper heating and ventilating of buildings, and little was really known about this extremely important scientific subject. But today the knowledge of it and its importance in regard to the great mass of people is becoming more fully realized, and rapid strides are being taken in the practical application of the principles of heating and ventilating. The demand for artificial heat depends on the climate of the country in which, and the character of the people to which, the heat is to be supplied. The proper temperature for a room in this country is 70 F. though a play-room, where active exercise is taken, may be heated only to 50 F. In England, on account of the extreme humidity of the atmosphere, it is not necessary to have such a high temperature. Artificial heat is necessary in our latitude during the greater part of the year. Heat is a sensible quality of objects. It may be measured by means of scientific instruments, but we can tell about it only as we compare a body with other bodies, i.e., a body is hotter or colder in comparison with another body. There is a certain law, well known to chemists, called the "law of diffusion of gasses", which states that if two gases are in contact, they will mix and inter-mix, until the resultant is a perfectly mixed or diffused combination of the gases. Another well-known law is that heated air expands. When heated air and cold are brought in contact with each other, since the hated air is expanded, it takes a greater bulk of the heated air to be the same quantity of cold, and so is also of a different quality than the unheated, by the law of diffusion of gases just stated, they will tend to mix, seeking equilibrium. These two facts are of extreme importance in the science of heating and ventilating buildings.
Citation: Blachly, Minerva. Heating and ventiliation. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Heating; Ventilation; Artificial Heat; Theses